ANALISIS KARAKTERISTIK BANGKITAN PERJALANAN PENDUDUK PERUMAHAN BARU BYPASS - Rahmadi, Ryan; Halim, Zulfuadi; Setiawan, Panji Eka; Junialdi, Yudi (FSTPT Indonesia, 2015)
Growth and development of the desert city that lasted until the current development of new settlements in the bypass due to reduced carrying capacity of the neighborhoods in the city center, which causes changes in land use are likely to spread. Construction of medium and large scale housing in bypass increases with the rate of population growth. Kelurahan river weaning, District Kuranji become one of the new housing growth point. One of the new housing that is located in the Village of the river weaning Housing jabal rahmah .Perumahan sustainable and have been selected to be a study area because it has a great potential trip generation. It can be seen from the number of houses which amounted to more than a thousand units of the houses are built which is a simple RSS or home healthy. That the higher seizure bypass region has the potential to cause problems such as traffic delays. There needs to be research on the residential trip generation in the bypass. The purpose of this study is to trip generation induced land use jabal rahmah sustainable housing. Movement or movement in one direction of travel is from the origin zone to the destination zone, including the movement of the foot (Tamin, 2000). In this study, the movement in question is a movement with the goal zone is outside the housing complex with purpose regardless of movement or travel. Average movement per day is calculated from the movement of households conducted by the movement of the weekly aggregated daily basis The method used in the study is a quantitative method with a quantitative analysis approach.